Interactive probiotics - Pessione, Enrica (CRC Press, 2014)
"This book underlines the importance of reciprocal interactions between probiotics and humans in terms of stress induction, epigenetic control of cellular responses, oxidative status, bio-active molecules biosynthesis, moonlighting proteins secretion, endogenous toxins neutralization, and several other biological functions. It explores how these responses can affect metabolism and metabolic-related disorders, gutbrain axis balance, mood, inflammatory, allergic and anti-infective reactions, cancer, and ageing. The book explores how probiotics create a dynamic and "fluid" network of signals able to control the balance between healthy and altered human status"--Provided by publisher.
Keywords: Probiotics.; elektronické knihy; electronic books